2023
DOI: 10.3389/fpain.2023.1159134
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Remission of chronic low back pain and oral dysesthesia comorbid with attention deficit/hyperactivity disorder by treatment with atomoxetine and pramipexole

Abstract: IntroductionOral dysesthesia is a disease characterized by pain and/or abnormal sensations in the oral region, without any organic abnormality. Its symptoms include pain, and it is considered to be a disorder associated with idiopathic oral-facial pain. It is also known that idiopathic oral-facial pain tends to coexist with chronic musculoskeletal pain, including low back pain, even before its onset. Such coexisting idiopathic pain conditions are also called chronic overlapping pain conditions (COPCs). In gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…However, if ADHD occurs in a patient with ASD, medications for ADHD are available. Consistent with the findings in this case, studies have reported that ADHD medications can significantly improve chronic pain (25)(26)(27)(28)(29)(30)(31). It has also been reported that ADHD is more likely to be associated with chronic pain (32)(33)(34).…”
Section: Discussionsupporting
confidence: 88%
“…However, if ADHD occurs in a patient with ASD, medications for ADHD are available. Consistent with the findings in this case, studies have reported that ADHD medications can significantly improve chronic pain (25)(26)(27)(28)(29)(30)(31). It has also been reported that ADHD is more likely to be associated with chronic pain (32)(33)(34).…”
Section: Discussionsupporting
confidence: 88%
“…This is because there are increasing reports that dopamine agonist treatment, such as pramipexole, improves both ADHD symptoms and chronic pain. 7 In addition, atomoxetine, which enhances noradrenaline and dopamine, was effective for both ADHD symptoms and comorbid unexplained orofacial pain. 4 Altered pain perception and comorbid chronic pain in patients with ADHD suggest dysfunction of the dopaminergic neurotransmission.…”
mentioning
confidence: 99%
“…Another comorbidity of ADHD, chronic pain syndromes such as fibromyalgia, migraine, and unexplained orofacial pain (burning mouth syndrome and persistent idiopathic facial pain), may be also closely related to the pathophysiology of ADHD. This is because there are increasing reports that dopamine agonist treatment, such as pramipexole, improves both ADHD symptoms and chronic pain 7 . In addition, atomoxetine, which enhances noradrenaline and dopamine, was effective for both ADHD symptoms and comorbid unexplained orofacial pain 4 .…”
mentioning
confidence: 99%